Integrated bioconversion process for biodiesel production utilizing waste from the palm oil industry. Issue 3 (June 2022) - Rachmadona, Nova; Harada, Yusuke; Amoah, Jerome; Quayson, Emmanuel; Aznury, Martha; Hama, Shinji; Kondo, Akihiko; Ogino, Chiaki
Abstract: This study was focused on utilizing palm oil industry waste to produce biodiesel. Palm acid oil and bioethanol partially concentrated from the distillation of artificial palm sap served as the feedstock. Thermomyces lanuginosus lipase (TLL) immobilized on the charcoal of coconut shells served as the biocatalyst in the trans-esterification reaction. After 48 h in bioethanol (63% v/v) obtained from the distillation of artificial palm sap, 500 mg of TLL, esterification at 40 ºC and 35 rpm yielded 98.1% w/w fatty acid ethyl ester. The evaluation of the Gibbs free energy (−10.1 kJ mol −1 ) showed that the reaction system proceeded spontaneously for producing biodiesel, and the activation energy (Ea) of this esterification process was 58.9 kJ mol −1 . This evaluation of biodiesel synthesis utilizing residual oil from palm oil mill effluent and the bioethanol from palm sap could establish the sustainability of an integrated approach to biorefinery operations and reduce the cost of the process. Further, a kinetic study on TAG and FFA was performed to elucidate the superiority of oil with a high FFA content for faster reactions than that with a high TAG in using bioethanol as the acyl acceptor. Graphical Abstract: ga1 Highlights: Integrated bioconversion utilizing palm oil waste was applied in practical process. Esterification using bioethanol from palm sap and PAO attained FAEE yield of 98.1%. The Gibbs free energy and activation energy of this esterification are determined. The use of waste could reduce the total estimated cost of biodiesel production.